2016
DOI: 10.1680/macr.15.00090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyacrylate/GO nanocomposites on properties of cement paste

Abstract: Polyacrylate/graphene oxide (GO) nanocomposites were prepared by the copolymerisation of GO with acrylic acid and acrylamide. The effects of polyacrylate/GO nanocomposites on cement paste fluidity and the microstructure and mechanical strength of hardened cement paste were investigated. The results indicate that the GO nanocomposites have no effect on cement paste fluidity and can efficiently control cement hydration products and its microstructure compared with using GO sheets directly. The corresponding hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, the morphology of GOCC sample is different with GPCC. The hydration products displayed a few flower-like structures, in accordance with previous literatures [15]. Lv et al [15] demonstrated that the flower-like hydration product crystals were controlled by GO.…”
Section: Mechanical Properties and Microstructure Of Gpcc And Goccsupporting
confidence: 88%
“…However, the morphology of GOCC sample is different with GPCC. The hydration products displayed a few flower-like structures, in accordance with previous literatures [15]. Lv et al [15] demonstrated that the flower-like hydration product crystals were controlled by GO.…”
Section: Mechanical Properties and Microstructure Of Gpcc And Goccsupporting
confidence: 88%
“…For example, Lu Z. and Li Z have co-authored in multiple publications[42,[54][55][56]. Lv S. has been leading the research within the cluster in multiple research outputs[4][5][6]15,41,[44][45][57][58][59]. Quantitative measurements provided in…”
mentioning
confidence: 99%
“…The smallest material is nano-scale graphene, which has the same size as cement hydration products. Cement hydration products can expand by bonding to graphene (Lv et al, 2016). Carbon black of micron grade can fill the pores of cement hydration products.…”
Section: Discussionmentioning
confidence: 99%